(untitled) (Iraqi Journal of Civil Engineering, 2008)
This study is the second stage of the paper “Study the Effect of Rubber Silicon on Physical Properties of Asphalt Cement”. This study took the effect of additives on asphalt mixture performance. Asphalt mixture has been designed by Marshall method for determining the optimum asphalt content and geophysics properties of mix according to ASTM (D- 1559 ). Rubber silicon at different percentage (1%, 2%, 3% and 5%) was added to asphalt binder and three specimens of asphalt rubber silicon mixture (ARSM) are prepared and evaluating according to Marshall method. Diametric tensile creep test ASTM (D-1075) at 60 Co used to evaluating permanent deformation and modulus of elasticity for ARSM. The study shown that the Rubber-Silicon has more effects increasing the marshal stability, air voids, and reducing the flow and bulk density compared with the original mix.. Increase the flexibility properties of the mix and this appear from reducing the permeate deformation at test temperature (60C), the reduction percent is about (30 to 70)%